The Influence of Education and Mental Health on the Choice of Sports Recreation by Adolescents - Nugroho, Budi Sulistiyo; Kusumawati, Prima Dewi; Br Sembiring, Lisma Natalia; Eli Sabrifha; Arlia (International Journal of Public Health Excellence (IJPHE), 2024)
The present study aimed to investigate the relationship between participation in sport and mental health through a literature review. While sport has long been recognized for its physical benefits, its impact on mental health has recently attracted greater attention. In order to analyze the literature addressing how sport affects mental health, both negatively and positively, a comprehensive search was conducted using data from journal articles, books as well as research reports published in the last two decades. It is crucial to maximize the benefits of exercise while minimizing the risks. This review reaffirms the significance of exercise as an efficacious intervention for mental health, underscoring the necessity for a balanced and informed approach to managing risks. Further research recommendations include longitudinal investigations of the long-term effects of exercise on mental health and studies of the psychological mechanisms behind its benefits. It is crucial to optimize exercise benefits while minimizing risks. This review corroborates the efficacy of exercise as an effective intervention for mental health and emphasizes the need for a balanced and informed approach to risk management. Further research is warranted to examine the long-term effects of exercise on mental health and to elucidate the underlying psychological mechanisms associated with its benefits.